Integrated Responsibility Due to Mining Activities to Environmental Crisis: Capturing Pers Opinion in Environmental Issues - Syahputra, Bearlly Deo (Indonesia Media Law Review, 2023)
This article was written so that investors could examine the obligations of the central government, territorial legislatures, financial backers, and the general public as a result of mining exercises during natural disasters. To recognize ecological justice, aggregate awareness must be demonstrated and acknowledged. Additionally, a lack of ecological issues can lead to multi-aspect emergencies like an increase in financial disparities and a decline in environmental quality. Ecological security is mandated by the 1945 Republic of Indonesia Constitution in Article 33 Paragraph 4, which takes into account carrying capacity standards and natural knowledge that is proportional to the people's economy. The methodology of this paper is qualitative. It deals with the legal problems that are happening right now. Green businesses have not yet been fully recognized by specific regulations. As a result, achieving a sense of fairness and legal certainty as a legitimate and desirable development will encourage the region to switch to control, long-term investments as a means of addressing the environmental crisis. It is everyone's responsibility to lessen the negative effects of mining investments in Indonesia, particularly on the environment.